KONSISTENSI TRADISI TAHLILAN DAN KENDURI DI KAMPUNG SAPEN PERSPEKTIF FENOMENOLOGI AGAMA - Dzulkifli, Mohammad (IAIN Kediri, 2021)
The article examines the sacred experience of the Sapen culture in interpreting and conserving the tahlilan and kenduti traditions. In the midst of globalization and urban life, The Sapen’s people from a decade ago continue to practice tahlilan in some circumstances. The aim of this article is to clarify the factors that contribute to the continuity of the tahlilan and kenduri traditions in the Sapen community through the lens of religious phenomenology. The study employs fieldwork, participatory observation, and interviewing techniques. The findings of this study indicate that three factors contribute to the continuity of the tahlilan and kenduri traditionsin Sapen. To begin, there is the influence of immigrants who used to practice tahlilan in their village. Second, cultural traits inherited from elders are passed down across generations. Third, a strong sense of brotherhood and peace among the Sapen peoples. Additionally, Tahlilan is viewed as a vehicle for citizens to interact and spread the message of Islam within the Sapen culture.Keywords: Sapen Village, Tahlilan, Phenomenology